GRADE 12 SENIOR HIGH STUDENTS MENTAL HEALTH MANAGEMENT IN THE MIDST OF COVID-19 PANDEMIC - Desiree L. Gildo (International Education Trend Issues, 2023)
This study has focused in detail on the mental health management of 25 Grade 12 students to collect the data, the researchers developed their questionnaire that was pilot tested in the selected Grade 12 students of schools found in the Urban and Rural schools in the Schools Division of Camarines Sur and Tagkawayan District Division of Quezon and distributed through Google Forms that spanned within the 2nd and 3rd week of May 2022. These findings from a qualitative study that used a survey form were sent to enrolled Grade 12 students and randomly answered about Grade 12 Senior High School Students on Mental Health Management in the Midst of the COVID-19 Pandemic to explore the ways in which Grade 12 Senior High school students who took part constructed their understanding of what constitutes mental Health Management in the Midst of Covid -19 Pandemic. In essence, they did so by drawing on their own experiences during the Covid-19 Pandemic. The study used a comparative & descriptive research design to understand the perspectives and challenges of Grade 12 Senior High School Students regarding their coping mechanisms adapted amidst pandemic. The result showed that meditation or reflection is their most effective coping mechanism in managing their mental health issues. And least indicate that the respondents identified their coping mechanism are focusing on positive thoughts. Thus, it concluded that Grade 12 Students are not just faced with the physical health risks that are brought about by this pandemic, but they are also afflicted with the mental aspect of their well-being as well, as the heavy burden of having to deal with processing how they would survive this difficult situation on their own, the uncertainty of their future, the difficulty of keeping up with their studies despite the limited resources and many other aspects that affects their mental health.